The Effect of Social Media on The Iraqi Slang: A Socio-Pragmatic Study - Batool Abdul-Mohsin Miri (UIN Salatiga, 2025)
Applying the socio-pragmatic approach to vernacular language emphasizes its central role in shaping social and cultural development. The study followed a targeted approach. First, inductive coding was conducted to identify recurring themes associated with colloquialisms. This development was then classified on the basis of the Hymes language model and Grice's implicature theories. Through thematic analysis, the study revealed how verbal language functions in different contexts. It reflects interpersonal relationships, social activities, and emotional expression. To ensure the reliability and consistency of the results, data from multiple sources, such as media and digital platforms, were considered. Hymes’ model showed how public discourse adapts to different situations, participant interactions, and communication purposes. On the other hand, Grice's semantic theories revealed the deeper meanings of these terms. Unlike Western studies, which mainly focus on irony, politeness, and efficacy of exchanges, this study identifies socio-pragmatic elements of the Iraqi slang. These elements include, for example, but not limited to, metaphorical expressions of dissent, humor, and indirect critique as a survival strategy in political or tribal contexts. This study shows how vernacular speech processes social relations, transmits cultural values, and delivers social critiques. By focusing on these features, the study fills the gap in non-Western socio-pragmatic research. Especially, the context-specific norms that are often ignored. It therefore provides a deep understanding of the Iraqi language as a versatile form of contextual communication.